(untitled) - Röpke, Wilhelm (Chicago, 1960)
An introduction to economic thinking which holds that the vital things in life are those beyond supply and demand, written by the chief architect of Germany's post-war social market economy. A Humane Economy offers an understandable and compelling explanation of how economies operate. A sweeping and brilliant exposition of market mechanics and moral philosophy, Rpke's masterwork cuts through the jargon and statistics that make most economic writing so obscure and confusing. Over and over, the great Swiss economist stresses one simple point: You cannot separate economic principles from human behavior.
Keywords: Công nghệ và văn minh,Technology and civilization